Respuesta :

Solution :

[tex]t = \frac{3}{20} [/tex]

Step-by-step explaination:

[tex] \frac{1}{3} t + \frac{4}{5} = \frac{3}{5} - t[/tex]

1. Substract 1/5 from both sides

[tex] \frac{1}{3} t + \frac{4}{5} - \frac{4}{5} = \frac{3}{5} - t - \frac{4}{5} [/tex]

2. Simplify

[tex] \frac{1}{3} t = - t - \frac{1}{5} [/tex]

3. Add t to both sides

[tex] \frac{1}{3} t + t = - t - \frac{1}{5} + t[/tex]

4. Simplify

[tex]4t = - \frac{3}{5} [/tex]

5. Divide both sides by 4

[tex] \frac{4t}{4} = \frac{ - \frac{3}{5} }{4} [/tex]

6. Simplify

[tex]t = - \frac{3}{2 0} [/tex]

Solution :

= [tex]t = - \frac{3}{20} [/tex]